2011
DOI: 10.1007/s00436-011-2457-6
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial potential of medicinal plant extracts from Malaiyur and Javadhu hills of South India

Abstract: The emergence and spread of Plasmodium falciparum with resistance to chloroquine (CQ), the safest and cheapest anti-malarial drug, coupled with the increasing cost of alternative drugs especially in developing countries have necessitated the urgent need to tap the potential of plants for novel anti-malarials. The present study investigates the anti-malarial activity of the methanolic extracts of 13 medicinal plants from the Malaiyur and Javadhu hills of South India against blood stage CQ-sensitive (3D7) and CQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 80 publications
0
23
0
12
Order By: Relevance
“…Previous reports demonstrate the antiplasmodial (Kamaraj et al, 2011) anti-diabetic (Gupta et al, 2010), larvicidal ) and anti-cancer (Prasanna et al, 2009) effects of leaf extracts of Cassia auriculata. Juan-Badaturuge et al (2011) isolated the antioxidant kaempferol-3-O-rutinoside, kaempferol, quercetin and luteolin from Cassia auriculata.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports demonstrate the antiplasmodial (Kamaraj et al, 2011) anti-diabetic (Gupta et al, 2010), larvicidal ) and anti-cancer (Prasanna et al, 2009) effects of leaf extracts of Cassia auriculata. Juan-Badaturuge et al (2011) isolated the antioxidant kaempferol-3-O-rutinoside, kaempferol, quercetin and luteolin from Cassia auriculata.…”
Section: Discussionmentioning
confidence: 98%
“…Our failure to demonstrate activity against P. falciparum (IC 50 > 64  μ g/mL) is not in agreement with literature data on other Solanum species. For example, Chinchilla et al [26] reported antimalarial effect for S. arboretum ; Kamaraj et al [27] found some effect for S. torvum against chloroquine-sensitive (3D7) and chloroquine-resistant strains of P. falciparum . Moreover, diosgenone which is a spirostan-type steroidal saponin isolated from S. nudum , showed a high activity against FCB-2 strain of P. falciparum [28].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed leaf extract from A. crassiflora was rich in flavonoids and alkaloids, and was able to reduce the Plamsodium berghei NK65 infection level in mice by 57-75% with a daily dosage of 12.5 µg/kg/day [62]. Another study of the crude methanol extract of A. squamosa indicated moderate activity against Plasmodium falciparum 3D7 with an IC 50 value of 30 µg/mL compared to the chloroquine control, which gave an IC 50 value of 0.021 µg/mL [63]. Moderate anti-plasmodium activity was also shown using crude extracts of A. muricata (Table 2).…”
Section: Antiprotozoal Activitiesmentioning
confidence: 99%